Health education needs of pregnant women regarding newborn inborn errors of metabolism based on a social ecological model: a qualitative study - Hao Yang; Fenghua He; Dan Xia; Xihong Wang; Yujia Guan; Hongqian Liu (Frontiers in Public Health, 2026)
Background This study explored pregnant women's perceptions, experiences, and health education needs regarding newborn inborn errors of metabolism (IEM) and newborn screening, and examined how these needs operate across individual, interpersonal/healthcare-organizational, and community/policy-environment levels. Methods A descriptive phenomenological qualitative design was used. Fifteen pregnant women (N1–N15) were purposively recruited from one national regional medical center between October 2025 and January 2026 for one-to-one, face-to-face, semi-structured interviews lasting 30–45 min. Two trained researchers conducted the interviews. Recordings were transcribed verbatim and managed in NVivo . Two researchers independently coded the data; unresolved disagreements were adjudicated by a third researcher. Data were analyzed using Colaizzi's seven-step method, and inductively generated themes were subsequently organized using a three-level consolidation of the social ecological model. All participants received their transcripts for verification, and the final three interviews confirmed thematic saturation. Results Three overarching analytic levels and 16 subthemes were identified. Individual-level needs concerned conceptual boundaries, screening value, personalized risk information, graded management of abnormal results, uncertainty-related psychological support, and probability communication. Interpersonal and healthcare-organization needs concerned time-linked flowcharts, result notification, operational checklists, repeat-testing/referral navigation, and family communication with privacy protection. Community and policy-environment needs concerned post-diagnosis support, affordability and assistance, authoritative information access, staged reminders, and understandable multimodal delivery. Participants' accounts showed that their needs extended beyond knowledge acquisition to actionable, time-sensitive pathways linking antenatal education with postnatal screening and follow-up. Conclusions Pregnant women's health education needs regarding newborn IEM are multi-level, time-sensitive, and action oriented. Interventions should combine plain-language risk communication and coping support at the individual level, family-inclusive communication and closed-loop service processes at the interpersonal/organizational level, and authoritative information, financial navigation, and accessible multimodal support at the community/policy level.